Differences in miRNA expression profiles between wild-type and mutated NIFTPs. Issue 10 (October 2017) - Denaro, Maria; Ugolini, Clara; Poma, Anello Marcello; Borrelli, Nicla; Materazzi, Gabriele; Piaggi, Paolo; Chiarugi, Massimo; Miccoli, Paolo; Vitti, Paolo; Basolo, Fulvio
Abstract : Noninvasive encapsulated follicular variants of papillary thyroid carcinomas have been recently reclassified as noninvasive follicular thyroid neoplasms with papillary-like nuclear features (NIFTPs). NIFTPs exhibit a behavior that is very close to that of follicular adenomas but different from the infiltrative and invasive follicular variants of papillary thyroid carcinomas (FVPTCs). The importance of miRNAs to carcinogenesis has been reported in recent years. miRNAs seem to be promising diagnostic and prognostic molecular markers for thyroid cancer, and the combination of miRNA expression and mutational status might improve cytological diagnosis. The aim of the present study was to evaluate the miRNA expression profile in wild-type, RAS - or BRAF -mutated NIFTPs, infiltrative and invasive FVPTCs, and follicular adenomas using the nCounter miRNA Expression assay (NanoString Technologies). To identify the significant Kyoto Encyclopedia of Genes and Genomes (KEGG) molecular pathways associated with deregulated miRNAs, we used the union of pathways option in DNA Intelligent Analysis (DIANA) miRPath software. We have shown that the miRNA expression profiles of wild-type and mutated NIFTPs could be different. The expression profile of wild-type NIFTPs seems comparable to that of follicular adenomas, whereas mutated NIFTPs have an expression profile similar to that of infiltrative and invasive FVPTCs. The upregulation of 4 miRNAs (miR-221-5p, miR-221-3p, miR-222-3p, miR-146b-5p) and the downregulation of 8 miRNAs (miR-181a-3p, miR-28-5p, miR-363-3p, miR-342-3p, miR-1285-5p, miR-152-3p, miR-25-3p, miR-30e-3) in mutated NIFTPs compared to wild-type ones suggest a potential invasive-like phenotype by deregulating the specific pathways involved in cell adhesion and cell migration (Hippo signaling pathway, ECM-receptor interaction, adherens junction, regulation of actin cytoskeleton, fatty acid biosynthesis and metabolism).